Investigating the Mediating Role of Self-Compassion and Cognitive Emotion Regulation in the Relationship Between Experiential Avoidance and Tendency Toward Extramarital Relationships Among Married Women - Ebrahimi, Hossein; Nowrozidoost, Ghazale (Mental Health and Lifestyle Journal, 2026)
The present study was conducted with the aim of examining a causal model of experiential avoidance, self-compassion, cognitive emotion regulation, and the tendency toward extramarital relationships among married women in the city of Shiraz. This research employed a correlational design within the framework of structural equation modeling. The statistical population consisted of all married women residing in Shiraz during the winter of 2025, from whom 250 individuals were selected through convenience sampling. Data were collected using the Whatley Tendency Toward Extramarital Relationships Questionnaire (2008), the Neff Self-Compassion Scale (2003), the Garnefski Cognitive Emotion Regulation Questionnaire (2001), and the Gámez Multidimensional Experiential Avoidance Questionnaire (2001). Data analysis was performed using SPSS version 24 and SmartPLS software. Findings from the model analysis indicated that all direct and indirect paths among the variables were statistically significant, and the model demonstrated an acceptable fit. Accordingly, it can be concluded that experiential avoidance, self-compassion, and cognitive emotion regulation exert significant effects on married women’s tendency toward extramarital relationships.